A review of the United Arab Emirates healthcare systems on medical tourism and accreditation - Alshamsi, Amna I. (Frontiers in Health Services, 2024)
This paper aims to review the healthcare system in the United Arab Emirates (UAE) and the utilisation of international accreditation to improve the quality of healthcare services and to grow its medical tourism industry. Medical tourism has contributed to the UAE's economy. Hence, the country mandated international accreditation in public and private facilities to attract patients and boost medical tourism. Accreditation is recognised worldwide as one of the main drivers for implementing quality and patient safety standards, which has sparked considerable interest in studying the effects and outcomes of such assessments. Therefore, the second aim of this paper is to review the UAE's strategic goals to improve the quality of healthcare services using international accreditation. Although striving to achieve global accreditation attracts tourists, it is essential to understand the needs and outcomes of such assessments. This review showed how the UAE healthcare sector has evolved to improve the quality of its healthcare services through accreditation. While enhancing the quality of such services and increasing the medical tourism industry provided many opportunities for expatriates to move to the UAE, the country should aim to strengthen its medical services by expanding to other Middle Eastern countries. This paper could influence policymakers implementing international accreditation in the UAE and the Middle Eastern region.